BEYOND BINARIES: ECO-SPIRITUAL UNDERTIDES IN SARA JOSEPH’S GIFT IN GREEN - Panicker, Joji John (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Sara Joseph’s Gift in Green (originally Aathi in Malayalam, translated by Valson Thampu) is a profound narrative that intertwines ecological consciousness with spiritual dimensions, offering a vision of harmony between humanity and the natural world. Set in the mythical village of Aathi, the novel employs the metaphor of “water-life” to symbolize the sacred interconnectedness of life, critiquing the patriarchal and capitalist forces that disrupt this balance. This essay explores the eco-spiritual undertides in Gift in Green, analyzing how Joseph integrates indigenous spiritualities, pantheistic worldviews, and ecological ethics to portray Aathi as a sacred space of resistance and renewal. Through characters like Shailaja, Kunjimathu, and Gauri, Joseph highlights the role of women as custodians of both ecological and spiritual wisdom, drawing parallels with global eco-spiritual movements. Engaging with theories from scholars like Vandana Shiva, Thomas Berry, and Starhawk, the essay examines themes of sacred ecology, communal rituals, and resistance against commodification. By situating Aathi’s struggle within broader environmental and spiritual discourses, the essay underscores the novel’s contribution to eco-spiritual literature, advocating for a holistic approach to ecological and social justice.